Supine arm cycling during the post-flap recovery period for persons with spinal cord injuries: The multi-purpose arm cycle ergometer (M-PACE) safety and pilot testing. (2nd January 2023) - Olney, Christine M.; Ferguson, John E.; Voss, Greg; Nickel, Eric; Fairhurst, Stuart; Bornstein, Alexandra S.; Kemmer, Sara; Stien, Crystal; Scheel, Kristin; Brenteson, Charlotte; Goding, Ann; Kruse, Mary Murphy; et al.
Abstract : Objective: To describe how using a supine arm cycle ergometer can safely reduce deconditioning experienced by patients with spinal cord injury or disorder (SCI/D) during their four to six weeks of complete bed rest after surgery to close a stage 4 pressure injury. Design: This pilot project used a newly designed arm cycle ergometer (known as the M-PACE) that extends over the bed, allowing a patient to lie completely supine while exercising. Setting: The M-PACE was designed and built at the Minneapolis Veterans Affairs Health Care System (MVAHCS) and pilot tested at the MVAHCS SCI/D Center. Participants: Patients with SCI/D, recovering from flap surgery and deemed appropriate to use the arm cycle ergometer were enrolled in the pilot study ( n = 47). Outcome Measures: A pre–post six-minute arm test (6MAT), a proxy for conditioning, was conducted on a subset ( n = 15) of participants before and after the supine cycling exercise training program. Participants' rating of perceived exertion (RPE) scores were collected at cessation of each 6MAT. Participants gave feedback on their perception of using the M-PACE. Results/Conclusions: The 6MAT RPE was significantly reduced after training with the M-PACE while on bed rest ( P = 0.003). Also, significantly more rotations were performed after completing the training program ( P = 0.02). Further, study participants who accessed the M-PACE found using it helped offset the tedium of laying supine during flap surgery recovery. The differences in the 6MAT pre- to post measures indicate the M-PACE should be further studied for offsetting the normal deconditioning that occurs with extended bedrest.